Terror as a Bargaining Instrument: A Case Study of Dowry Violence in Rural India - Bloch, Francis; Rao, Vijayendra (American Economic Review, 2002)
Terror as a Bargaining Instrument: A Case Study of Dowry Violence in Rural India by Francis Bloch and Vijayendra Rao. Published in volume 92, issue 4, pages 1029-1043 of American Economic Review, September 2002